Kemampuan Pemecahan Masalah Geometri Siswa berdasarkan Self-Regulated Learning - Syarifah, Rif'atul; Permadi, Hendro; Qohar, Abdul; Anwar, Lathiful (Edumatica : Jurnal Pendidikan Matematika, 2023)
One of the subjects that can measure students' problem solving abilities is geometry because geometry discusses objects, definitions, symbols and images that can be used as ideas or ideas by students. This research is a descriptive qualitative study which aims to describe and analyze students' ability to solve problems based on Polya's steps in terms of self-regulated learning (SRL). The subject of this research is one student in each SRL (high, medium, low). Data collection methods are questionnaires, tests and interviews. The results showed that 12.5% of students had high SRL levels, 70.83% had medium SRL level students and 16.67% had low SRL level students. Students with high SRL can complete problem solving according to Polya's steps. Students with moderate SRL can apply the steps of understanding the problem (writing the information available and what is being asked) and the planning steps. Meanwhile, students with low SRL can understand the problems in the questions. Based on interviews students can only provide information from what is contained in the questions but do not have ideas to solve them. Students with low SRL are only able to do the first of the four stages of problem solving. So, it can be concluded that the higher the SRL or the level of one's learning independence, the higher the ability to solve problems.